AERODYNAMIC ANALYSIS IN THE DESIGN OF AN ELECTRIC VEHICLE MODEL TOBACCO STYLE M-164 WITH COMPUTATIONAL FLUID DYNAMIC (CFD) METHOD - Azamataufiq Budiprasojo; Mochammad Reza Firmansyah (Jurnal Rekayasa Mesin, 2022)
The aerodynamic aspect is one of the most important things in the automotive sector which is used to find information on the performance of an aerofoil model design. The performance of an aerofoil through streamflow associated with fuel consumption which means the higher the air speed, the greater the resistance received, so that the fuel consumption will be greater. At this case, fuel consumption can be reduced by creating an aerofoil model design that maintain great aerodynamic to minimize drag forces. The affects of streamflow around the vehicle are discussed in this papper. This research simulated 3D electric vehicle Tobacco Style M-164 in steady condition with various velocities, i.e. 50 km/h, 60 km/h, 70 km/h, and 80 km/h. This simulation use the Tethahedron mesh model and run in SST k-omega turbulence model. The affects can be observed with the quantitative and qualitative data. The quantitative data used as measurable data were Maximum Fluid Pressure, Drag Force, and Coefficient of Drag (CD). The quantitative data is shown to provide a better visual explanation of the streamflow affects. The qualitative data shown in this paper are velocity contours, vectors, and pathlines. The value of the maximum fluid pressure and drag force is directly proportional to the increase in velocity stream. The coefficient of drag decreased as the free stream increased with a percentage decrease of 2.48%. The average value of the coefficient of drag (CD) from this research was 0.318.